IT literacy in Kampung Jenjarom / Muhammad Fais Abdullah - Abdullah, Muhammad Fais (2006)
This research is purposely done to determine the level of IT literacy in Kampung Jenjarom society. It is also to identify the factors that lead to IT literacy in Kampung Jenjarom. Beside, the researcher also proposes solution in increase the IT literacy levels in Kampung Jenjarom. Questionnaires were distributed to the Kampimg Jenjarom society. On the whole, it can be said that Kampung Jenjarom society already has novice skills regard IT. Meanwhile, the factors determined IT literacy in Kampung Jenjarom was- computer ownership rate, monthly income, education level, English usage, and Intemet accessibility.